Accurate cisAB typing is essential to ensure the safety of a transfusion: A case of a cisAB01 neurosurgery pediatric patient and family study - Yanan Zhang (Wiley, 2021)
Abstract The rare cisAB subgroups inherited from a single parent are characterized by the activities of dual A and B glycosyltransferases encoded by a gene on one chromosome. The serological complexity of cisAB challenges clinical blood transfusion practice because of misclassification in ABO grouping.